Outcome comparison of primary trapeziectomy versus secondary trapeziectomy following failed total trapeziometacarpal joint replacement - Kaszap, Balázs; Daecke, Wolfgang Heinz Manfred; Jung, Martin (The journal of hand surgery. [American volume], 2013)
Purpose - To compare the clinical outcome between secondary trapezial excision after failed total trapeziometacarpal joint replacement and primary trapeziectomy. - Methods - Between October 2003 and July 2008, we performed 16 revision procedures in our institution because of failed trapeziometacarpal joint replacements. Of these patients, 15 were followed up. We compared clinical outcomes between this group and 15 patients treated with primary trapeziectomy in a matched-pair analysis. The matching criteria were sex, age, and time from surgery. The mean follow-up period was 48 months. We evaluated mobility (radial and palmar abduction, opposition, and Kapandji score), grip strength, and patient self-assessment (pain; satisfaction; Disabilities of the Arm, Shoulder, and Hand score; and activity restriction). - Results - According to most of the clinical evaluation methods (range of motion and Kapandji score) and subjective assessments (pain; Disabilities of the Arm, Shoulder, and Hand), outcome did not differ considerably between the 2 study groups. In particular, the results of strength testing were not significantly different between groups. - Conclusions - The present study showed that the outcomes of secondary trapeziectomy after failed trapeziometacarpal joint replacement arthroplasty generally do not differ from the primary trapeziectomy results. Although it shows high revision rates in the literature, trapeziometacarpal total joint arthroplasty might be a treatment option. In the case of failure, the outcome of secondary trapeziectomy is comparable to that of primary trapeziectomy. - Type of study/level of evidence - Therapeutic III.